Digital Model in Orthodontics: Is It Really Necessary for Every Treatment Procedure? A Scoping Review - Ioanna Pouliezou; Anastasia Panagiota Gravia; Michail Vasoglou (MDPI AG, 2024)
Digital models and three-dimensional technology in orthodontics have become an integral part of everyday clinical practice. Nevertheless, there is currently no consensus regarding in which cases a digital model is really necessary. Therefore, this scoping review aims to identify and assess which orthodontic procedures require a digital model. This review's reporting was based on PRISMA guidelines. A literature search was undertaken using five electronic databases on 17 February 2024. A total of 87 studies met the inclusion criteria and were qualitatively analyzed by three reviewers. The following aspects of orthodontic treatment were identified and discussed with regard to digital model application: diagnosis, treatment procedures, retention, and outcome evaluation in orthodontics. Based on the studies assessed, despite some limitations regarding radiation exposure justification and the accuracy of the integration methods of 3D data, there is evidence that digital models lead to more accurate orthodontic diagnosis and treatment planning. In cases of impacted canines, aligner treatment, mini-implants insertion (when angle definition and orientation are essential), and primary care for cleft lip and palate, a partial digital model produced by an integration of some of the 3D data (face scan, intraoral scan, CBCT) that we can acquire is beneficial. A full digital model that combines all the 3D information should be used in orthognathic surgery cases, in which prediction and accurate performance are highly advocated.